Analyses Coûts-bénéfices des packages agroécologiques chez les producteurs, les collecteurs et les transformateurs de la chaîne de valeur lait de Bobo-Dioulasso - Sib, Ollo; Orounladji, Boko Michel; Ouattara, Songdah Désiré; Traore, Issouf; Sanogo, Souleymane; Vall, Eric (2024)
In Burkina Faso, the Initiative on Agroecology (IAE) is helping stakeholders in the Dairy Innovation Platform ('Plateforme d'Innovation Lait', PIL) achieve the dairy value chain's agroecological transition, taking the PIL's vision - which was defined in 2020 (during Africa-Milk), then reviewed and confirmed in 2023 at the beginning of the IAE (due to its compatibility with the principles of agroecology) - and putting it into action. In 2023, the PIL was further consolidated by integrating new partners who could provide valuable support towards the dairy industry's agroecological transition. As part of the IAE, we are working within this space known as the Agroecological Living Landscape (ALL), which focuses on the dairy value chain. For 'ALL' players, the ultimate goal is "to increase the share of local milk in dairy products manufactured by Bobo-Dioulasso dairy processors, through innovations at farm level, in milk collection and processing, and in the governance of the dairy value chain". The idea behind the IAE's involvement is to support the co-design of an agroecological business model for the dairy value chain which could integrate all of these innovations based on the key principles of agroecology in order to guarantee the sustainability and resilience of this value chain. To this end, IAE researchers support ALL stakeholders in co-designing changes (innovations) at different levels of the food system: • At farm level: by strengthening agriculture-livestock integration in dairy production units to sustainably increase milk production (forage production and co-product recycling into fodder and manure) • At collection level: through diversifying collector services, and especially milk collection centres, in order to increase milk collection in terms of quantity, quality and consistency • At processing level: by diversifying dairy products to meet growing consumer demand These changes are based on a range of practices that we call agroecological packages. We are therefore working on 3 main packages: 1) the agroecological production package (forage crops, organic manure, etc.); 2) the agroecological collection package (diversification of services to farmers and processors); 3) the agroecological processing package (diversification of dairy products). To guide the ALL’s implementation in an agroecological transition, the main objective of the IAE in Burkina Faso is to co-design an Agroecological Business Model (Ae BM) for the dairy value chain with ALL stakeholders. As shown in Figure 1, this work falls specifically within the scope of the IAE’s WP3. However, the findings of all the other work packages (1 to 4) will need to be taken into account in the development of this agroecological business model. The ‘Cost-Benefits Analyses of agroecological packages’ workshops for farmers, collectors and processors within Bobo-Dioulasso’s dairy value chain (CBA workshops) represent a further step in the process of co-building the Ae BM.